Differences in ball speed and accuracy of tennis groundstrokes between elite and high-performance players - Landlinger, J.; Stöggl, T.; Lindinger, S.; Wagner, H.; Müller, E. (European Journal of Sport Science, 2012)
The main aim of this study was to identify and compare ball speed and hitting accuracy of forehand and backhand groundstrokes between ATP professionals (elite) and high-performance youth players when shots were played cross-court and down the line to a target square. Six elite and seven high-performance tennis players volunteered to participate in the study. A Doppler-radar device and a digital video camera, operating at 120 frames per second, were used to measure ball speed and accuracy of forehand and backhand groundstrokes in the respective situation (cross-court and down the line). The results of 1040 measured groundstrokes indicate that the ball speed of the forehand and the backhand ground stroke was higher in the elite group when analysing (1) all valid shots, (2) the six fastest shots, and (3) the six most accurate shots (all P < 0.05). In addition, all players achieved a higher forehand speed compared with their backhand when balls were directed cross-court (P < 0.01). The participants demonstrated similar ability when considering accuracy of their groundstrokes (P > 0.05). However, a group difference for accuracy was identified when considering the six fastest forehand shots (P<0.05), and the forehand cross-court stroke was played more accurately than the backhand cross-court stroke by both groups (valid shots and six most accurate shots, P<0.05). Moreover, there was no evidence that players who impacted the ball faster were any less accurate than those who impacted the ball more slowly. Analyses for participants actually revealed a negative correlation between ball speed and mean radial error (accuracy) for the backhand down the line (r= - 0.77, P<0.01). According to the results of this study, ball speed seems to be the determining factor that separates elite from sub-elite tennis players.